2020
DOI: 10.3390/ijms21207734
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PtrMYB121 Positively Regulates the Formation of Secondary Cell Wall in Arabidopsis thaliana

Abstract: MYB transcription factors have a wide range of functions in plant growth, hormone signaling, salt, and drought tolerances. In this study, two homologous transcription factors, PtrMYB55 and PtrMYB121, were isolated and their functions were elucidated. Tissue expression analysis revealed that PtrMYB55 and PtrMYB121 had a similar expression pattern, which had the highest expression in stems. Their expression continuously increased with the growth of poplar, and the expression of PtrMYB121 was significantly upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Also, numerous MYB TFs enhance cell-wall properties and wood formation. For example, PtrMYB121 directly binds to and activates the promoters of genes related to lignin and cellulose synthesis, thus regulating SCW formation [ 117 ]. PtrMYB152, the homolog of the Arabidopsis R2R3-MYB TF AtMYB43, acts as a specific transcriptional activator of lignin biosynthesis during the formation of poplar wood.…”
Section: Regulation Of Mybs In Lignificationmentioning
confidence: 99%
“…Also, numerous MYB TFs enhance cell-wall properties and wood formation. For example, PtrMYB121 directly binds to and activates the promoters of genes related to lignin and cellulose synthesis, thus regulating SCW formation [ 117 ]. PtrMYB152, the homolog of the Arabidopsis R2R3-MYB TF AtMYB43, acts as a specific transcriptional activator of lignin biosynthesis during the formation of poplar wood.…”
Section: Regulation Of Mybs In Lignificationmentioning
confidence: 99%
“…The regulatory roles of some poplar R2R3-MYB genes in drought response have been reported. For example, recent studies have demonstrated that PtrMYB121 (Potri.002G185900) and PtoMYB170 (Potri.005G001600) can promote the accumulation of lignin and cellulose, and PtoMYB170 enhances drought tolerance by triggering stomatal closure [ 17 , 63 ]. As a transcriptional activator, PtrMYB94 (Potri.017G082500) was involved in the transcriptional regulation of the expression of ABA and drought stress-related genes (e.g., ABA1 , DREB2B , and P5CS2 ), thereby improving the tolerance of transgenic A. thaliana plants to drought stress [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MYB59 is identified in A. thaliana to be involved in the transcriptional regulation of secondary xylem formation [ 43 ]. Several transcription factors have also been identified in poplar associated with secondary wall development, such as Poplar PtrMYB2, PtrMYB3, PtrMYB20, and PtrMYB21 [ 44 ]; (Homologs of MYB46 and MYB83 in A. thaliana ), PtrMYB55, and PtrMYB121 [ 45 ]; (Homologs of MYB55 in A. thaliana ), PtoMYB92, and PtoMYB125 [ 46 ]; (Homologs of MYB85 in A. thaliana ), PtoMYB170 [ 47 ], and PtoMYB216 [ 48 ]; and (Homologs of MYB61 in A. thaliana ) were identified to be involved in regulating secondary cell wall formation. Conversely, PtrMYB6 [ 49 ], PtoMYB156 [ 50 ], PtrMYB189 [ 51 ], and PdMYB221 [ 52 ] had inhibitory effects on lignin accumulation.…”
Section: Discussionmentioning
confidence: 99%